ANTIPYRETIC EFFECTIVENESS OF METHANOL EXTRACT OF NONI (Morinda citrifolia L.) LEAVES ON INDUCED BREWER’S YEAST - Koten, Maria Rosalia Sigo (Jurnal Mahasiswa Kesehatan, 2022)
Fever is an increase in body temperature above the normal body temperature (36°-37° C). Fever is overcome by the administration of antipyretic supply (paracetamol), can also use tradisional medicines from medicinal plants such as noni leaves. This research aims to find out the antipyretic effect of methanol extract of noni  leaves (Morinda citrifolia L.) on white mice in the induction of Brewer's Yeast. The extract was prepared by maseration method using methanol as a solvent. Mice were divided in 5 treatment groups. Each mice was  induced with Brewer's Yeast at a dose of 112 mg / 20 grams of body weight for mice. The first group in the CMC given 1% as negative control, the second group was given Paracetamol as a positive control, the 3rd, 4th and 5th were given noni leaf extract at a dose of 50 mg / KgBB, a dose of 150 mg / KgBB, a dose of 250 mg / KgBB. Temperature measurement were  carried out for 3 hours at intervals of 30 minutes. Measurement data were analyzed statistically using ANOVA test (Analisys Of Variance) with Anova one way method. The results of the research were obtained, that methanol extract of noni leaves can reduce the temperature of fever. The best dosage as an antipyretic is a dose of 250 mg / KgBB.  Key words:Antipiretic, methanol extract, Noni leaf(Morinda citrifolia L), Brewer's Yeast